Isolation and characterization of lantanillic acid from lantana camara l. In Bangladesh - Khan, Abira; Kuddus, Md Ruhul; Rashid, Mohammad A; Hossain , Md Sakhawat; Uddin, Md Aftab (Bangladesh Journal of Botany, 2025)
Lantana camara L. is an important medicinal plant with potential medicinal values and rich phytochemical composition. Lantanillic acid (1), an oleanane type triterpene, was isolated from the ethyl acetate extract of leaves of L. camara grown in Bangladesh. The structure of this compound was established by analysis of1H NMR, 13C NMR and mass spectroscopic data and comparison with published values. Bangladesh J. Bot. 54(3): 465-468, 2025 (September)